Futuro à vista: transição para a vida adulta de adolescentes e jovens adultos brasileiros com paralisia cerebral sob a ótica biopsicossocial - Santana, Camila Araújo Santos (Universidade Federal de São Carlos, 2024)
This thesis has as its central theme the process of transition to adulthood for adolescents and young adults with cerebral palsy. Due to the state of evidence on the topic at a global and national level, different methodological approaches were adopted throughout the doctoral period, resulting in three articles. Article 1: Aimed to synthesize the literature regarding the components of the International Classification of Functioning, Disability and Health (ICF) that have been addressed, looking beyond body structures and functions, and to analyze who was evaluated in research on adolescents and young adults (AJA ) with cerebral palsy (CP) in the transition phase to adulthood. It was concluded from this scoping review including 86 studies that the constructs related to activity and participation are the main research focus of the studies available in the literature between 2014 and 2021 that explored factors related to the development of health, autonomy and participation, with more needed studies that focus on environmental factors. Teenagers and young adults are the main source of information and the perspectives of other key figures are also being considered. Article 2: This cross-sectional study aimed to describe the levels of autonomy in participation in ten areas of adult life and explore factors associated with autonomy in participation of young Brazilians with cerebral palsy (CP). 114 young people with CP participated in the study, and it was observed that autonomy in participation is in development or complete in most areas of life. Romantic relationships and sexuality were the areas with the lowest levels of autonomy, while rehabilitation and leisure presented high levels of autonomy. Levels of autonomy tended to increase along with greater perceived self-efficacy and age, with personal factors playing a central role in the acquisition of autonomy in participation during the transition to adulthood for young people with CP. Article 3: Aimed to understand the most relevant participation experiences for these young people, and to support the development of a questionnaire to explore these aspects with young people with CP transitioning to adulthood in a larger study. Using qualitative and participatory methodology, it was possible to develop a questionnaire containing 25 questions. The experiences lived and reported by young people were essential to identify specificities about the most relevant themes that supported the development of the questionnaire, and the partnership with them in research occurred in a dynamic and effective way. Based on these three studies, it was observed that a more comprehensive view of human development is necessary when we research, evaluate and monitor adolescents and young adults with cerebral palsy who are in the transition phase to adulthood. Your opinions about your own experiences and health condition should be considered as a priority whenever possible. Your environmental context must also be considered as a major influencer on your process of becoming an adult. Their acquisition of autonomy in participation can be increasingly supported and promoted as they grow, and their personal empowerment will also enable them to be more autonomous and to engage in diverse activities, including scientific research, and will also allow them to reach their participation potential and enjoy the best possible quality of life.
Future in sight: transition to adulthood of Brazilian adolescents and young adults with cerebral palsy from a biopsychosocial perspective
Keywords: Paralisia cerebral; Transição para a vida adulta; Revisão de escopo; Autonomia em participação; Envolvimento do público em pesquisa; Cerebral palsy; Transition to adulthood; Scoping review; Autonomy in participation; Public involvement in research; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL